Proposing Criteria for Assessing the Sustainability of Residential Buildings in Syria and Measuring their Application - ميا, رنا; حسن, رفاء (Latakia University Journal -Engineering Sciences Series, 2021)
The sustainability of the buildings reduces the impact of the built environment on the natural environment and improves the effectiveness of the building to ensure a high quality life for future generations as it is one of the most important topics that have been focused on in recent times. The objective of the research is to develop criteria for evaluating the sustainability of buildings that fit the reality of the implementation of buildings in Syria and to test their suitability by evaluating a sample of residential buildings implemented in Syria. The evaluation process is carried out through the design of a measuring tool to measure the level of implementation of sustainability in residential buildings projects and distribution to a sample of engineers within the Design and implementation specialists. The most important criteria were set for the conditions of Syria. The criteria were divided into seven axes. Using the five-dimensional Likert scale and determining the relative importance of each axis. The study concluded that the most important criteria in both design and implementation stages are energy efficiency as well as the economic side where the most important criteria can be utilized in designing an model for sustainable housing.